Information Behavior of Umsida Students on Social Media - Nurhayati (Universitas Airlangga, 2023)
ABSTRACT Social media is an integral part of student life, given its enormous use as a source of information. This study examines student behavior in interacting with information using the Wilson (2000) behavioral model. This research was conducted at Universitas Muhammadiyah Sidoarjo by using a descriptive qualitative method, namely by explaining the student information behavior at Universitas Muhammadiyah Sidoarjo. Analysis of information behavior begins with an analysis of information needs. The main drivers for the creation of information needs are personal motives, namely cognitive and affective, as well as relational motives. In cognitive-based motivation, social media is used to increase knowledge which can improve self persona, both appearance and skills. The affective-based motivation is the need for sources of entertainment. Social media becoming a tool for students to express and establish their social relationship, to build an image, connecting themselves and to be a part of a group. The search for information is active, because social media provides a variety of interconnected platforms, so that information can be displayed in detail and clearly. The behavior of information utilization by students of Universitas Muhammadiyah Sidoarjo also shows their awareness of the information quality, so that a verification process is implemented to test the information accuracy. PERILAKU INFORMASI MAHASISWA UMSIDA DI MEDIA SOSIAL ABSTRAK Pemanfaatan media sosial sebagai sumber informasi semakin jamak dikalangan mahasiwa sehingga kajian mengenai perilaku informasi di media perlu dilakukan agar kita memperoleh gambaran pasti bagaimana informasi dibutuhkan, dicari, diolah dan dimanfaatkan. Penelitian ini menunjukkan bahwa perilaku pencarian informasi muncul karena dorongan kebutuhan yang disebabkan oleh motif personal dan relasi sosial. Pada motif personal, informasi diperlukan untuk meningkatkan ketrampilan, memperbaiki penampilan, menunjang kegiatan akademik dan bisnis hingga memenuhi tuntutan hobi. Adapun relasi sosial, informasi diperlukan untuk menunjukkan identitas diri, membangun citra, membangun dan mengembangkan hubungan serta menjadi bagian dari komunitas yang diikuti. Pencarian informasi lebih mengarah pada pencarian secara aktif dengan menggali informasi lebih dalam dari berbagai macam sumber di media sosial untuk mendapatkan informasi secara cepat dan akurat. Verifikasi informasi menjadi bagian penting yang selalu dilakukan mahasiswa UMSIDA sebelum informasi yang didapat tersebut dimanfaatkan dan dibagikan dengan cara melihat keterbaruan isu, asal sumber informasi, dan tingkat akurasi berita.